(untitled) (Anwer Khan Modern Medical College Journal, 2019)
Background: Water is basic human right, most precious resource for economy and health. Drinking water and sanitation is a fundamental health service. The health of a person largely depends on its quality and quantity of safe water. Water must be safe and wholesome. But unfortunately the problem of water pollution has now become a burning question. Objective: To explore the knowledge and practice of drinking safe water among the community people. Method: This was a descriptive type of cross-sectional study conducted at Horintana, Khulna, during the period from January 2018 to April 2018 to assess the Knowledge and practice of drinking safe water among the villagers. The respondents were adult population of the community. Result: Most of the respondents were in 30-44 years age group, (53.64%) and 15-29 years age group (31.36%). Majority of the respondents were female (84.55%). Majority of villagers drank tube well water (93.64%). 81.36% of the respondents knew about safe sources of drinking water. 14 (6.36%) respondents, who used water other than tube well water applied purification methods. A large portion of respondents (14.09%) did not know about the water borne diseases. Among the water borne diseases they had suffered,most prevalent diseases were diarrheal diseases (57.63%) and parasitic infestations (16.66%). In most cases, treatment providers were MBBS doctors (64.23%). Conclusion: In conclusion, the study revealed that the knowledge and practice of safe drinking water among the rural people is now satisfactory. But the matter of great sorrow is that, the socio-economic condition and educational status of people is hampering towards the good health. Anwer Khan Modern Medical College Journal Vol. 10, No. 2: July 2019, P 105-109